Modeling and simulation of biomass gasification processes - Paiva, Mateus Vinicius (2020)
Biomass gasification is the conversion of organic materials into an energetic gas, rich in hydrogen and carbon monoxide, through oxidation and reduction reactions at elevated temperatures. In the evaluation of gasification processes, estimating the composition of the fuel gas for different conditions is fundamental to identify the best-operating conditions. In this way, gasification modeling and simulation provides an analysis of the process performance, allowing for resources and time savings in pilot-scale process operation, as it predicts the behavior and analyzes the effects of different variables on the process. Thus, the focus of this work was the modeling and simulation of biomass gasification processes using the UniSim Design chemical process software, applying the tools available in the simulator database in order to satisfactorily reproduce a downdraft gasifier operation behavior. The study was done for two residual biomasses (forest and agricultural) in order to predict the produced syngas composition. The reactors simulated gasification by minimizing Gibbs free energy. The main operating parameters were the equivalence ratio, steam to biomass ratio and gasification temperature (independent variables). In the simulations, a sensitivity analysis was carried out, where the effects of these parameters on the syngas composition, syngas flow and heating value (dependent variables) were studied, in order to maximize these three variables in the process with the choice of the best parameters of operation. The model is able to predict the gasifier's performance and is qualified to analyze the behavior of the independent parameters in the gasification results. In summary, with a temperature between 850 and 950°C, SBR up to 0,2 and ER between 0,3 to 0,5, the best operating conditions are obtained for maximize the composition of the syngas rich in CO and H2.